New Neotropical species of Ceraeochrysa Adams (Neuroptera: Chrysopidae) - Sosa, Francisco; De Freitas, Sergio [UNESP] (Magnolia Press, 2010)
Species of Ceraeochrysa Adams are distributed from southeast Canada to Argentina. Larvae feed on aphids, thrips, white flies, mites, and neonatal larvae of Lepidoptera in varied agroecosystems. Seven species are known in Venezuela, viz. Ceraeochrysa achillea Freitas & Penny, C. angulata (Navas), C. bitacornua Freitas & Penny, C. caligata (Banks), C. cubana (Hagen), C. everes (Banks), and C. valida (Banks). In this study, three species are described as new to science, Ceraeochrysa melaenopareia sp. nov., Ceraeochrysa pittieri sp. nov., and Ceraeochrysa torresi sp. nov.
Keywords: Biological control; Chrysopinae; Chrysopini; green lacewing; natural control